Multirotor sizing methodology with flight time estimation - Biczyski, Marcin; Sehab, Rabia; Whidborne, James F.; Krebs, Guillaume; Luk, Patrick Chi-Kwong (Wiley/Hindawi, 2020)
This paper addresses the need for sizing of rotors for multirotor vehicle applications such as personal air transport, delivery, surveillance, and photography. A methodology for the propeller and motor selection is developed and augmented with flight time estimation capabilities. Being multirotor-specific it makes use of the platform’s simplicity to rapidly provide a set of off-the-shelf components ready to be used in the vehicle. Use of operating points makes the comparison process fast, precise, and tailored to specific application. The method is easily implemented in software to provide an automated tool. Furthermore, clearly defined input and output parameters make it also usable as a module in other multicriteria optimisation algorithms. The new methodology is validated through comparison with a consumer-grade drone and the calculated results are compliant with manufacturer’s specification in terms of maximum hover time.